Migration of Population in the Northern Border Regions of Azerbaijan - Abdullayeva, Gulnara Islam (Київський національний університет імені Тараса Шевченка, 2023)
Purpose. The main purpose of the research work is to study the migration features of the population in the northern border regions of Azerbaijan, to identify existing problems in this area and to identify ways to solve them. Method. Comparative analysis, attractiveness of the area, statistical methods were used in writing the article. The northern border regions of the Republic of Azerbaijan were chosen as the research object. Conclusion. Despite the implementation of several state programs from 2004 until now, there is inequality in the socio-economic development of the regions of the Republic of Azerbaijan. Unlike the Baku-Absheron zone, there are still serious problems in the socio-economic life of the population in other regions. This leads to an increase in unemployment and poverty in the regions, migration of the population to Baku. Since the border regions are of strategic importance for the state, more attention should be paid to the employment of the population in order to keep them on the ground. Taking into account the strategic importance of the border position of the northern border regions of the Republic of Azerbaijan and the extreme natural conditions in the mountainous area, it is necessary to give certain concessions to the population living here for the sustainable socio-economic development of the border settlements. The creation of certain infrastructures should be carried out directly at the expense of the state, and for their continuous, constant activity, it is advisable to have these enterprises under state control. Scientific novelty. Demographic development and participation of the population in the migration process in the northern border regions of Azerbaijan were studied. As a result of these studies, it was found that in some settlements, as a result of the decline in natural growth and migration, the population has sharply decreased. The recommendations and suggestions given in the article are important for determining the strategic importance of population settlement in the northern border regions and eliminating existing problems in the field of demographic development.
Keywords: population; border regions; migration; demography. Azerbaijan